Analysis of the Quality and Quantity of Dug Well Water in Sifnana Village, South Tanimbar District, Tanimbar Islands Regency - Eferista Ngilawane; Edward Gland Tetelepta; Roberth Berthy Riry (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
This study aims to analyze the quality and quantity of well water in Sifnana Village, South Tanimbar District, Tanimbar Islands Regency. Dug wells are the community's primary source of clean water, especially due to insufficient PDAM services. However, there is variation in the water quality produced by these wells. Some wells provide water that is odorless, colorless, and tasteless, while others are contaminated by dirt and coliform bacteria. Factors such as the distance between wells and pollution sources and environmental cleanliness significantly affect water quality. Regarding quantity, tidal fluctuations also play a major role, with well water levels decreasing drastically during low tides. Therefore, the community must improve well maintenance and environmental sanitation to ensure the water quality remains safe for consumption